Mechanisms of Regulated Cell Death: Current Perspectives. Issue 4 (July 2021) - Santagostino, Sara Francesca; Assenmacher, Charles-Antoine; Tarrant, James C.; Adedeji, Adeyemi O.; Radaelli, Enrico
Balancing cell survival and cell death is fundamental to development and homeostasis. Cell death is regulated by multiple interconnected signaling pathways and molecular mechanisms. Regulated cell death (RCD) is implicated in fundamental processes such as organogenesis and tissue remodeling, removal of unnecessary structures or cells, and regulation of cell numbers. RCD can also be triggered by exogenous perturbations of the intracellular or extracellular microenvironment when the adaptive processes that respond to stress fail. During the past few years, many novel forms of non-apoptotic RCD have been identified, and the characterization of RCD mechanisms at a molecular level has deepened our understanding of diseases encountered in human and veterinary medicine. Given the complexity of these processes, it has become clear that the identification of RCD cannot be based simply on morphologic characteristics and that descriptive and diagnostic terms presently used by pathologists—such as individual cell apoptosis or necrosis—appear inadequate and possibly misleading. In this review, the current understanding of the molecular machinery of each type of non-apoptotic RCD mechanisms is outlined. Due to the continuous discovery of new mechanisms or nuances of previously described processes, the limitations of the terms apoptosis and necrosis to indicate microscopic findings are also reported. In addition, the need for a standard panel of biomarkers and functional tests to adequately characterize the underlying RCD and its role as a mechanism of disease is considered.